The Use of STEM as a Tool for Teaching the Concept of Magnetism in Kindergarten - Vasiliki Samara; Konstantinos T. Kotsis (Scientia Publica Media, 2025)
This study explores the integration of STEM education as a tool for teaching the concept of magnetism to kindergarten children. The research highlights the importance of engaging young learners through hands-on activities and creative storytelling, which allows them to express their understanding of magnetism based on their everyday experiences. The findings indicate that children initially possess misconceptions about magnets, such as believing that they attract all metals and that larger magnets are inherently stronger than smaller ones. Children are guided to correct these misconceptions and better understand magnetic properties through structured activities, such as drawing objects attracted and repelled by magnets. Artificial intelligence tools, such as ChatGPT and ideogram.ai, facilitate collaborative storytelling, enabling children to create illustrated narratives about magnets and enhancing their engagement and creativity. The study also emphasizes the role of technology in supporting children’s learning processes, allowing them to visualize and present their findings innovatively, such as through videos and presentations. Moreover, the research identifies the need for further exploration of children’s interactions with magnets and the effectiveness of AI in teaching complex scientific concepts to preschoolers. The results suggest that active participation in STEM activities significantly boosts children’s confidence and interest in science, laying a foundation for future engagement in STEM fields. Overall, this paper contributes valuable insights into the pedagogical strategies that can enhance the teaching of magnetism in early childhood education, advocating for the continued integration of technology and creative methods in the learning process.